Implementation of a universal rotavirus vaccination program: comparison of two delivery systems - Zelman, Mitchell (BioMed Central, 2014)
BACKGROUND: Rotavirus vaccine is recommended for all infants in Canada. To evaluate the logistics of implementing a universal rotavirus vaccination program, we compared the effectiveness of program implementation in jurisdictions with either a physician-administered or public health nurse-administered program. METHODS: All infants born between October 1, 2010 and September 30, 2012 in Prince Edward Island and Nova Scotia’s Capital District Health Authority were eligible for the vaccination program. A universal rotavirus vaccination program was implemented and delivered in public health clinics in Prince Edward Island and in physicians’ offices in Nova Scotia. RESULTS: Engagement of vaccinators in delivery of the universal vaccination program was more successful in Prince Edward Island than in Nova Scotia. Vaccine coverage rates rose rapidly in Prince Edward Island, exceeding 90% for both doses within 3 months and remaining at those levels over the two-year program. In contrast, coverage rates in Nova Scotia rose more slowly and never exceeded 40% during the two years. Access to coverage data was more timely and accurate in Prince Edward Island than Nova Scotia. CONCLUSION: A universal rotavirus vaccination program delivered through public health clinics achieved more rapid and higher levels of coverage than a program administered through physicians’ offices. TRIAL REGISTRATION: NCT01273077.